Pengaruh Harga, Promosi, dan Kualitas Pelayanan Terhadap Minat Beli Ulang Konsumen: Studi Kasus pada Hari-Hari Swalayan Bekasi Cyberpark - Ardinia, Fitria (Journal Business Inovation, Accounting and Management, 2025)
Hari-Hari Swalayan is one of the local retail businesses operating in the midst of the highly competitive modern retail industry. To maintain customer loyalty, an effective marketing strategy is essential, particularly in the aspects of price, promotion, and service quality. This study aims to examine the influence of price, promotion, and service quality on consumer repurchase intention at Hari-Hari Swalayan Bekasi Cyberpark. A quantitative approach with an explanatory research design was employed. Data were collected through questionnaires distributed to 100 respondents selected using purposive sampling. The data were analyzed using multiple linear regression, t-test, F-test, and classical assumption tests with the assistance of SPSS version 23. The results show that price, promotion, and service quality have a simultaneous significant influence on repurchase intention. Partially, promotion and service quality have a significant influence, while price does not significantly affect repurchase intention. These findings are expected to serve as a reference for retail business practitioners in formulating marketing strategies that focus on customer satisfaction and repeat purchases.